2008
DOI: 10.1074/jbc.m800161200
|View full text |Cite
|
Sign up to set email alerts
|

TIP60 Represses Transcriptional Activity of p73β via an MDM2-bridged Ternary Complex

Abstract: TIP60, a histone acetyl transferase, acts as a p53 coactivator by interfering with MDM2-mediated degradation of p53. However, little is known about its functional regulation of p73, which has structural features similar to p53. In this study we found that TIP60 represses apoptosis, which is induced by exogenous and endogenous p73␤. TIP60 also negatively regulated the expression of p73␤ downstream target genes such as p21 and Bax. Moreover, the specific repression of p73␤-mediated transactivation by TIP60 was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Despite the tumor suppressor activities of p73, only a few types of human tumors have been reported to harbor p73 mutations [27], which implies that other types of molecular mechanisms might be responsible for the deregulation of p73 during oncogenesis. Recently, it has been revealed that sirtuin (SIRT1), a member of sirtuin family of proteins [28], SHP-2 tyrosine phosphatase [29] and TIP60 histone acetyl transferase [30] disrupt p73 transactivation activity that leads to attenuation of p73-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the tumor suppressor activities of p73, only a few types of human tumors have been reported to harbor p73 mutations [27], which implies that other types of molecular mechanisms might be responsible for the deregulation of p73 during oncogenesis. Recently, it has been revealed that sirtuin (SIRT1), a member of sirtuin family of proteins [28], SHP-2 tyrosine phosphatase [29] and TIP60 histone acetyl transferase [30] disrupt p73 transactivation activity that leads to attenuation of p73-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Tip60 associates with transcription factors such as HIV-1 Tat, androgen receptors, and p53 as a coactivator (2,15,24,53,54). In contrast, it is also implicated in the negative regulation of gene expression through binding to STAT3, CREB, and p73 (16,28,60). Moreover, Tip60 mRNA is highly expressed in the early stages of neural retina development (55).…”
mentioning
confidence: 99%
“…In other cases, TIP60 directly acetylates the transcription factor, such as p53, to modulate transcriptional activity. 9) On the other hand, TIP60 has also been implicated in the negative regulation of gene expression through its binding to STAT3, 10) cAMP response element-binding protein (CREB), 11) and p73β 12) Despite the increasing number of studies of TIP60, the roles of TIP60 in regulating gene expression from specific promoters are not well understood.…”
mentioning
confidence: 99%